2019
DOI: 10.1186/s12935-019-0994-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Circular RNA ITCH suppressed prostate cancer progression by increasing HOXB13 expression via spongy miR-17-5p

Abstract: BackgroundCircular RNA Itchy E3 ubiquitin protein ligase (Circ-ITCH) is significantly down-regulated in various kinds of tumors, however, the mechanisms of action and functions of circITCH gene in prostate cancer (PC) are still under investigation. The mail goal of this research was to study the functional role of Circ-ITCH gene in prostate cancer and to illuminate the function role of circ-ITCH gene in prostate cancer by targeting miR-17-5p/HOXB13.MethodsRT-qPCR was applied to measure the expression level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 43 publications
3
47
1
Order By: Relevance
“… 38 In a recent study, circ-ITCH promoted prostate cancer growth, invasion, and metastasis by regulating the miR-17-5p/HOXB13 axis. 39 Moreover, circRNAs are also involved in many CNS-associated diseases. In the mouse stroke model obtained by transient middle cerebral artery occlusion, circDLGAP4 functioned as an endogenous miR-143 sponge to increase the expression of the miR-143 target HECTD1, thus decreasing infarct area and BBB damage.…”
Section: Discussionmentioning
confidence: 99%
“… 38 In a recent study, circ-ITCH promoted prostate cancer growth, invasion, and metastasis by regulating the miR-17-5p/HOXB13 axis. 39 Moreover, circRNAs are also involved in many CNS-associated diseases. In the mouse stroke model obtained by transient middle cerebral artery occlusion, circDLGAP4 functioned as an endogenous miR-143 sponge to increase the expression of the miR-143 target HECTD1, thus decreasing infarct area and BBB damage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the pooled HRs with their 95% CIs showed that low circ-ITCH expression was also signi cantly correlated with poor OS, implying that low circ-ITCH expression may serve as an indicator of unfavorable prognosis of cancers. Meanwhile, it has been demonstrated that ectopic expression of circ-ITCH was capable of inhibiting cancer growth in vivo [11,16], hinting that circ-ITCH might be a potential approach for cancer treatment. Taken together, circ-ITCH could serve as a biomarker for predicting the progression and outcome of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…22, was reported to be lower expressed in several cancers [10]. So far, circ-ITCH has been proved to be implicated in prostate cancer [11,12], ovarian cancer [13][14][15], bladder cancer [16], breast cancer [17], lung cancer [18], gastric cancer [19], hepatocellular carcinoma [20], glioma [21] and multiple myeloma [22]. Although the correlation between circ-ITCH expression and cancer progression has been investigated by these studies above, most individual studies have been limited by inconsistent conclusions or small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…215 One recent study have found that circITCH was significantly down-regulated in PCa cells and tissues, and inhibited the malignant phenotype of PCa via increasing the expression of homeobox protein B13 (HOXB13) through sponging miR-17-5p. 216 Likewise, circRNA-UCK2 inhibited cell proliferation and invasion via increasing tet methylcytosine dioxygenase 1 (TET1) expression by sponging miR-767-5p in prostate cancer. 217 Similarly, circFOXO3 sponged miR-29a-3p, circABCC4 sponged miR-1182, circHIPK3 sponged miRNA-338-3p and miR-193a-3p, and circAMOTL1L sponge dmiR-193a-5p were also reported in other studies.…”
Section: Prostate Cancermentioning
confidence: 99%